BUSINESS PERFORMANCE MANAGEMENT; AN IMPLEMENTATION MODEL - Suparto Darudiato (CogITo Smart Journal, 2020)
The competitions in industries are very intense nowadays, because of that, a system that can easily use and quickly provide information needed. In recent times, ICT is a part of the company's strategy. This paper will discuss the relation of the company's strategies and their ICT implementation, which used to create knowledge for decision-making. Based on the literature research and interview that have been done so far, a Business Performance Management if formulated into a model can easily monitor the achievement of the company